Ensiklopedi keris - Harsrinuksmo, Bambang (Jakarta : Gramedia Pustaka Utama, 2004)
Encyclopedia of daggers in Indonesia and other Southeast Asian countries.
Includes index.
Keywords: Daggers -- Indonesia -- Encyclopedias